STUDI TENTANG COULOMB STRESS PASKA GEMPA BUMI PADA DAERAH MAMUJU – MAJENE MENGGUNAKAN METODE DInSAR - Suprapto, Bambang Harimei; Maria, Maria; Arif, Samsu (Universitas Muhammadiyah Gorontalo, 2024)
Earthquake analysis has been carried out on January 8, 14 and 15 2021 based on changes in the Coulomb Stress Value and post-earthquake surface deformation in the Mamuju – Majene area using the DInSAR method, while the results of the research show changes in positive and negative coulomb stresses ranging from 0.2 bar to 1.0 bar and this positive coulomb tension change may trigger nearby earthquakes located at a distance of 5 km to 35.52 km. The earthquake that occurred on January 8, 1984 had four lobe sections consisting of two positive lobe areas trending northeast-southwest from the epicenter and two negative lobe areas trending northwest-southeast. The January 14 2021 earthquake increased the coulomb voltage in a relatively north-south direction. While the area that shows a decrease in coulomb voltage is relatively east. As well as the January 15 2021 earthquake, the area where the dominant increase in coulomb stress occurred was in the northwest-southwest direction. After the earthquake, there was a post-earthquake land surface change, the area that experienced the highest land level rise or uplift occurred in Kec. Kaluku and Bonena which range from 0.12514 m to 0.269211 m. While the Mamuju city area experienced an uplift ranging from 0.02375 m to 0.06655 m, while the Kec. Tapalang, Kec. Malunda, Kec. Ulamanda, Kec. Pamboang, as well as the coastal area of Majene Regency, most of the area is experiencing subsidence ranging from -0.1629 m to -0.0190 m.